Model and Simulation of Solar-Powered PEM Water Electrolysis for Green Hydrogen and Environmental Assessment in the Ibukota Nusantara - Parluhutan Siahaan; Sulistyo Sulistyo; Endang Kusdiyantini (Journal of Bioresources and Environmental Sciences, 2026)
Energy demand in Indonesia continues to rise in line with population and economic growth. Using Jakarta city of Indonesia, as a representative case, energy consumption in the transportation sector has risen significantly from year to year. This escalation contributes to deteriorating air quality and poses adverse impacts on public health. To prevent similar condition in the new capital city (Ibukota Nusantara - IKN), this study examines green hydrogen production to support Fuel Cell Electrical Vehicle (FCEV)-based transportation. The objective of this research is to evaluate the technical, economic feasibility and environmental benefit of a solar PV -power-driven Proton Exchange Membrane Water Electrolyzer (PEMWE) system for large-scale hydrogen generation in IKN. A dynamic PEMWE model was developed and simulated using MATLAB/Simulink/Simscape under operating temperatures of 60 °C, 80 °C and 100 °C at a current density of 1.2 A/cm2. Key performance indicators evaluated include membrane water diffusion flux, electro-osmotic drag, hydrogen production rate and system efficiency.  Result show that operation 80 °C achieves the optimal performance. Scaled-up calculations indicate a hydrogen output of 3,006.62 kg/day with an electricity demand of 143,617 kWh, resulting in specific energy consumption of 47.9 kWh/kg outperforming the commercial PEMWE range 51-55 kWh/kg. This production capacity can fuel approximately 1,500 FCEVs corresponding to a potential CO2 emission reduction of 13,112.7 kg CO2-eq/day. Economic analysis using the Levelized Cost of Hydrogen (LCOH), with a 6% WACC and 20-years project life, yields an annualized CAPEX of roughly MUSD 31 and electricity dominated OPEX of KUSD 577 per year. The resulting LCOH od USD 3.0/kg H2 aligns with projected 2030 green hydrogen cost target. In conclusion, Solar PV -powered PEMWE development in IKN is demonstrates holistic feasibility in term of technical viable, economically competitive and environment impactful.